Highly Stable Single Crystals of Three‐Dimensional Porous Oligomer Frameworks Synthesized under Kinetic Conditions. (28th May 2021) - Hou, Linxiao; Shan, Chuan; Song, Yanpei; Chen, Sifan; Wojtas, Lukasz; Ma, Shengqian; Sun, Qi; Zhang, Lin
Abstract: Various robust, crystalline, and porous organic frameworks based on in situ‐formed imine‐linked oligomers were investigated. These oligomers self‐assembled through collaborative intermolecular hydrogen bonding interactions via liquid–liquid interfacial reactions. The soluble oligomers were kinetic products with multiple unreacted aldehyde groups that acted as hydrogen bond donors and acceptors and directed the assembly of the resulting oligomers into 3D frameworks. The sequential formation of robust covalent linkages and highly reversible hydrogen bonds enforced long‐range symmetry and facilitated the production of large single crystals, with structures that were unambiguously determined by single‐crystal X‐ray diffraction. The unique hierarchical arrangements increased the steric hindrance of the imine bond, which prevented attacks from water molecules, greatly improving the stability. The multiple binding sites in the frameworks enabled rapid sequestration of micropollutant in water. Abstract : Various porous organic single crystals were self‐assembled via intermolecular hydrogen bonding, based on in situ‐formed oligomers linked by imine bonds that appeared via condensation between tetratopic amine and ditopic aldehyde compounds. These structures were noted to remain sufficiently robust even after guest removal, and offered accessible porosity that was comparable, or even superior, to that of other COF materials.